Constructing an air quality detection system using embedded system - Ngiam, Kee Tiong (2023)

(untitled)
This project includes developing hardware and software for the cloud platform, IoT network, and embedded system, and the project will concentrate on constructing and implementing an embedded system for air quality detection. The project will implement the IoT to monitor devices, collect data, and communicate with users. Various sensors will be used to track several types of gases, including carbon monoxide, ammonia, and particle matter levels, also involving temperature and humidity tracking. The calibration of the sensor will be applied before constructing the air quality detector. Sensor calibration aims to verify the sensor's precision and reproducibility of detection instruments. The IoT platform Blynk will prototype, deploy, and manage connected electronic devices at any scale and provide the user with a real-time air quality status.